POSSIBILITIES OF WIDE USE OF PRACTICAL METHODS OF TEACHING CHEMISTRY FOR ORGANIZING QUALITY EDUCATION (Conferencea, 2022)
This article is devoted to the wider use of opportunities for chemical experiments in the educational system, approaches to modified, reworked experiments based on a new didactic purpose. In chemistry education, the organization of experiments suitable for topics taught only by theoretical methods increases students' interest in science and helps to form creative, critical, and creative thinking skills.